LEGAL REGULATION OF ECONOMICS AND FINANCIAL LITERACY - Evatov Elomon O‘tkir o‘g‘li (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. Legal regulation of the economy and financial literacy are fundamental components of a modern and sustainable economic system. This study examines the interrelationship between legal frameworks and financial literacy in shaping economic stability, protecting consumer rights, and promoting efficient financial behavior among citizens. It highlights how state-regulated legal mechanisms ensure transparency, stability, and accountability within financial systems, thereby improving the investment climate and stimulating economic growth. The research also explores the increasing importance of financial literacy in the context of digital transformation, where new financial instruments such as electronic payment systems, online lending, and digital assets require updated legal norms and enhanced consumer protection mechanisms. Special attention is given to the role of institutions, education systems, and financial organizations in improving public financial knowledge and promoting responsible financial decision-making. Furthermore, the study analyzes international experiences and their relevance to national contexts, particularly focusing on Uzbekistan’s ongoing reforms in financial modernization and inclusion. The findings emphasize that the integration of strong legal regulation with comprehensive financial education contributes significantly to economic resilience, risk reduction, and sustainable development.